Insumos para a regulamentaç\~ao do funget: Informaç\~oes sobre execuç\~oes na justiça do trabalho - André Gambier Campos; Roberto Di Benedetto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper has two main purposes. Firstly, to provide information about the obstacles faced by Brazilian Labor Justice in making its decisions really effective. Secondly, to offer data which may help to estimate the amount of money involved in no-complied decisions. Regarding this, the paper provides information to calculate the amount necessary to implement Funget (a fund especially dedicated to improve the effectiveness of decisions in Labor Justice). This fund, created in the middle of the legal reform of Brazilian justice (Constitutional Amendment no 45/2004), demands a modest amount of money, what may ease its implementation in the near future.
Keywords: K00; K40; K49; 330; Labor Justice; No-Complied Decisions; Funget